MULTI DIMENSIONAL DYNAMIC SCENE ANALYSIS. MULTIDIMENSIONAL IMAGE OBJECT SEGMENTATION AND TARGET TRACKING - Iliev, Panayot; Tzvetkov, Plamen; Petrov, George (International Journal of Computing, 2014)
This paper presents an unconventional approach for object racking using image statistical criteria and 3D image entropy sequence analysis. The experimental results prove that the relationship between statistical characteristics of the 3D image entropy sequences and process of motion estimation is a guarantee for creating reliable and high precision target detection and tracking system. Using 2D and 3D multistage entropy functions analysis provide us a better way to reduce sequence channels for tracking moving and non moving objects. Vector based approach is used for object searching and detection inside image sequences. This way we provide necessary information for object based image sequences compression format that is much more efficient than standard MGEG video stream. Object based compression format is much more acceptable for high demanding security and military systems.